Social Presence Vs. Scarcity: Which Drives Generation Z Purchase Intention More in Live Streaming Commerce? Evidence From an Emerging Market Perspective - Esther Praja Anggriany Panggabean; Yusniar Lubis; Robert Tua Siregar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study intends to examine the influence of Social Presence and Scarcity on Purchase Intention of Generation Z in the context of live streaming commerce in Medan City. The strategy employed is quantitative with an explanatory design, employing data from 130 respondents who were picked by a purposive sample technique. Data analysis was performed using Structural Equation Modeling based on Partial Least Squares (PLS-SEM). The results reveal that Social Presence has a positive and significant effect on Purchase Intention, which means that social interaction, host presence, and community involvement in live streaming might improve customer purchase intention. Furthermore, Scarcity has a positive and significant effect, although its contribution is lower than Social Presence, demonstrating that scarcity pressure and time restrictions are still relevant stimuli to influence purchase decisions. At the same time, the two variables can explain 56.5% of the variation in Purchase Intention, hence the research model has moderate to strong predictive ability. This research highlights the significance of the Stimulus-Organism-Response (SOR) theory in the context of social commerce and for Generation Z, who are extremely responsive to real-time digital interactions. These findings have substantial implications for digital firms to create more effective live streaming commerce strategies based on social experiences.